EFEKTIVITAS PELAKSANAAN KELAS IBU HAMIL TERHADAP PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG PENCEGAHAN STUNTING DI DESA PUKDALE, KECAMATAN KUPANG TIMUR, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Maria Magdalena Theofila Duka; Avelina Paskalia Gusman (Jurnal Medicare, 2025)
Stunting is a condition of growth failure caused by chronic malnutrition, particularly during the first 1,000 days of life. Its risk factors begin during pregnancy, such as inadequate nutritional intake and limited maternal knowledge about health and nutrition. This study aimed to determine the effectiveness of prenatal classes in improving pregnant women’s knowledge about stunting prevention. The research employed a quantitative approach with a true experimental one-group pretest–posttest design. The sample consisted of 17 pregnant women in their second and third trimesters in Pukdale Village, selected through simple random sampling. Data were analyzed using the Wilcoxon test. The results showed an increase in maternal knowledge after attending prenatal classes, with a significance value of p = 0.005. The conclusion of this study is that the implementation of prenatal classes is effective in increasing pregnant women’s knowledge in efforts to prevent stunting.